Efficacy And Safety Of Systemic Antifungal Agents In Chronic Dermatophytosis -An Open Trial - Nirmala S; Shanker B; Sentamilselvi G; Janki C (Wolters Kluwer Medknow Publications, 2000)
Forty patients comprising of 20 males and 20 females suffering from dermatophytosis for more than one year and who were not on any topical or systemic medication 3 months prior to the institution of therapy, were divided into 4 groups, each comprising of 5 males and 5 females, were given oral griseofulvin 250 mg twice daily for 8 weeks for group A, oral ketoconzole 200mg daily for group B, oral fluconazole 150 mg twice weekly for group C and oral itraconazole and fluconazole were most effective drugs. Griseofulvin and itraconazole were found less effective. All the four drugs did not give rise to any side effect.